Extraction of essential oils from Caryocar Coriaceum (pequi) by enzymatic pathways (Research, Society and Development, 2021)
The species Caryocar Coriaceum (pequi), as it is popularly known, is a fruit that in some regions is widely used in Brazilian popular cuisine. In addition to having a peculiar taste, the oil extracted from the fruit brings health benefits and is widely used in popular medicine. Given the above, this study aimed to analyze, through an experiment with a qualitative approach, the economic viability of extracting essential oils from pequi by enzymatic route. Through the suspension of the fungus, Rhizopus Microsporus, the best fermentation time of 72 hours and the most efficient hydrolytic activity were established, so that the pequi oil extraction technique was carried out using the multienzymatic cellulase extract. After performing all these steps to obtain the oil, either through enzymes or water, it was observed that the enzyme, Rhizopus Microsporus, has a great activity for the extraction of essential oil from pequi, when compared to wet-distillation only with oil and water. Thus, the use of the filamentous fungus, Rhizopus Microsporus, can be a viable alternative in the extraction of essential oils, making the process more economical by reducing the extraction time and energy of the process and being environmentally correct, in other words, made the process of extracting the oil smaller, since, with the enzyme, it expands this extraction.